The Strength of RAFT (Role, Audience, Format, Topic) Strategy with Google Classroom in the Teaching Writing - Annisa Rahmasari; Saiful Rifa'i (Journal of Development Research, 2022)
The aim of the research was to conduct an investigation of the strength of the RAFT (Role, Audience, Format, Topic) Strategy and Google Classroom when applied in teaching writing. This sort of research employed a non-random sample from all student demographics using a non-randomized pretest-posttest control group design. Since a control group for the study was actually impossible to obtain, a quasi-experimental design was adopted. The study was applied in SMPN 1 Kanigoro Blitar, 2021–2022 academic year. The student of two classes, VII F and VII G, from which the treatment class was chosen by lottery served as the research subject for this study. Class VII G becomes the control class group and receives the conventional style of instruction, while class VII F served as the experimental class group that received the RAFT Strategy with Google Classroom treatment. ANCOVA was used to try and lessen some of these discrepancies as these groups differed on various criteria. According to study and data analysis, the research hypothesis was accepted and the null hypothesis was rejected as a consequence of data calculations. It could be concluded that the Role, Audience, Format, And Topic (RAFT) technique can have a big impact on students' capacity to create descriptive texts.